SOSIALISASI PEMANFAATAN BUAH NANAS SEBAGAI PROBIOTIK BAGI ANAK REMAJA DISEKOLAH SMA BATUBARA - Hidayat Sihotang, Supran; Sembiring, Fanny Rizki; Febriani, Yessi; Razali, Mariany; Apriani, Alya; Ulayya, Nasywa (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2025)
Pineapples (Ananas comosus) contain fiber, water, natural carbohydrates, minerals, vitamins, and the enzyme bromelain. This community service activity aimed to educate 50 students of Batubara High School (SMA Batubara) about the use of pineapple as a natural probiotic source. The program aimed to increase their knowledge and raise awareness about reducing their consumption of unhealthy foods and fast food, thus promoting a healthy digestive system. This program utilized participatory and educational methods. Prior to the presentation, the Tjut Nyak Dhien University community service team evaluated the program using pretests and posttests. The purpose of the pretest was to measure the extent of knowledge of grade X and XI students regarding the use of pineapple as a probiotic. Then, after the presenter delivered the material using power point and infocus media, he conducted a demonstration and showed probiotics that could be used immediately. The community service team conducted a posttest to see the extent of the increase in participants' understanding from the socialization provided. The results of this socialization activity showed a significant increase in (1) the assessment category of attitudes and awareness of digestive health where the pretest value had an average value of 35% and the posttest was 90%; (2) the assessment category of the content and benefits of pineapple increased by 80% with a pretest value of 30% (3) the probiotic assessment category also increased by 85% with a pretest value of 25% (4) the probiotic assessment category from pineapple increased by 87% with a pretest value of 30%. This outreach program is expected to not only increase students' understanding of probiotics but also foster sustainable healthy lifestyle habits among adolescents, as the fermentation process promotes healthy digestion, especially for those who frequently consume unhealthy foods.